EFFORTS TO ARRANGE TRADERS BASED ON ECONOMIC ZONES TO IMPROVE CONSUMER ACCESSIBILITY AND COMFORT IN GOWA REGENCY - Rifai, Mesrawati; Hasnawati, Hasnawati; Riswan, Riswan; B, Jalil; R, Musdalipa; Makduani, Rivai; Hiljati, Hiljati; Salam, Karta Negara (Yayasan Education and Social Center, 2025)
This community service activity aims to support efforts to organize traders based on economic zones in order to improve accessibility and consumer comfort in Gowa Regency. The background of the activity is based on the problem of suboptimal trader arrangement, characterized by low spatial order, obstacles to pedestrian access, and decreased consumer comfort in traditional trading areas. The method used is a participatory and collaborative approach through the stages of problem identification, economic zoning design, mentoring and educating traders, and monitoring and evaluation. The results of the activity indicate that the implementation of economic zoning can improve stall order, improve area accessibility, and create a cleaner and more comfortable trading environment. In addition, active participation of traders in the arrangement process increases a sense of ownership and compliance with the zoning agreement. From the consumer perspective, this arrangement has a positive impact on ease of access and shopping comfort. This activity is based on an adaptive and contextual economic zone-based trader arrangement model, and has the potential to be replicated in other regions. Overall, this service contributes to strengthening the local economy, improving the quality of public spaces, and the sustainability of trader businesses in Gowa Regency.